Fermentation of Fall‐oat Balage over Winter in Northern Climates. Issue 1 (8th January 2016) - Coblentz, Wayne K.; Muck, Richard E.; Cavadini, Jason S.
Abstract : The effects of below‐freezing temperatures on silage fermentation are poorly understood. Recently, several studies have evaluated the efficacy of producing fall‐grown oat ( Avena sativa L.) as an emergency silage crop within central Wisconsin; this late‐season forage option is attractive because the yield potential is good, and these forages also may accumulate significant amounts of sugar following frost events. 'Vista' oat from two field sites was harvested at the boot (Experiment 1) or early‐heading (Experiment 2) stages of growth, and then baled and ensiled in plastic film on 15 Nov. 2013. Bales were sampled over the winter and spring, concluding with a final sampling date of 15 May. Generally, there was little evidence of silage fermentation before internal bale temperatures exceeding 32°F, which occurred on 15 and 13 April for Experiments 1 and 2, respectively. During the final month of sampling, the respective pH of these silages declined to 4.61 and 5.71 for Experiments 1 and 2, and substantial amounts of ethanol were produced in each case (5.82 and 4.85%); however, lactic acid production was much greater for Experiment 1 (4.82%) than for Experiment 2 (1.63%). Silage fermentation within both experiments likely included significant activity by anaerobic yeasts, which metabolize sugars, thereby yielding ethanol and CO2 . These results indicate that silage fermentation can be delayed until spring by below‐freezing temperatures within the ensiled forage mass, and the high sugar content of these oat forages (≥21.0%) can encourage the production of ethanol, likely through activity of anaerobic yeasts.